Analisis Tingkat Pemahaman Santriwati Terhadap Materi Fi’il Menurut Keadaan Waktu Dalam Pembelajaran Shorof - Anisa Sepina Ulfa; Langgeng Sutopo; Khairil Anwar (Program Studi Pendidikan Bahasa Arab, 2022)
The objective of this research is motivated by the lack of proper use of nahwu and shorof techniques, such as the use of dhomir which is still not in accordance with the intended object, sentence structure that still follows Indonesian rules, the use of fi'il which is still reversed, fi'il madhi becomes fi'il. 'il mudhori or vice versa, it is difficult to distinguish fi'il according to the dhomir, and it is still difficult to distinguish the types of fi'il according to time. This research aims to describe the level of students' understanding of fi'il material according to the circumstances of the time in learning shorof students of class 2 KMI A. This type of research is descriptive qualitative, which aims to explain current events in the field. This research was carried out at the Al-Mujtama 'Al-Islami Putri Islamic Boarding School in grade 2 KMI Odd Semester in the 2020/2021 academic year. This research uses data collection by observation, tests, interviews, and documentation. The results showed that the level of understanding of students in grade 2 of KMI A on fi'il material according to the circumstances of the time in shorof learning was good. As for what causes female students to not understand the material because internal factors and external factors.. The conclusion in this research is that the students of grade 2 KMI A have understood the material according to the circumstances of the time with the category value above the KKM standard. So that the female students have understood the fi'il material according to the circumstances of the time well.